2015
DOI: 10.1097/bot.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Operative Treatment for Noncomminuted Humeral Shaft Fractures

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 27 publications
2
74
0
2
Order By: Relevance
“…The functional outcome achieved in our study is comparable to that in other similar studies on this topic 789101314152122). Compared to the normal opposite side used as a reference, most patients recovered their original ROM and strength.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The functional outcome achieved in our study is comparable to that in other similar studies on this topic 789101314152122). Compared to the normal opposite side used as a reference, most patients recovered their original ROM and strength.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the classical intramedullary nailing is minimally invasive, but it has the main drawback of potentially damaging the rotator cuff and causing shoulder impingement 1351011). The ABP is designed to combine the best features of these two techniques: therefore, it is minimally invasive and cosmetic friendly and causes minimal manipulation of vital structures 1012131415)…”
mentioning
confidence: 99%
“…Experience has shown that this pattern is associated with a high risk of failure with regard to simple fractures3444. However, extensive studies have shown that the MIPO technique used with a bridging plate can provide adequate stability even for simple fractures6111314. In our study, all simple fractures healed with some but not much callus.…”
Section: Discussionmentioning
confidence: 45%
“…It provides adequate stability and is a safe, effective method for both comminuted and simple fractures6111314. However, the type of plate fixation that works best for MIPO is not clear.…”
mentioning
confidence: 99%
“…The risk of bias of the included non-RCTs evaluated with the Newcastle–Ottawa Scale score is demonstrated in Table 1. Ten RCTs [10,11,13,16,18,19,2123,25] and 7 prospective studies [12,14,15,17,20,24,26] were included, and a summary of their characteristics is presented in Table 2. These studies were published between 2000 and 2015.…”
Section: Resultsmentioning
confidence: 99%